The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1097/01.aog.0000235711.11817.8c
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Factor VIIa to Successfully Manage Disseminated Intravascular Coagulation From Amniotic Fluid Embolism

Abstract: The use of recombinant activated factor VIIa in cases of massive hemorrhage, such as in our patient, is controversial but has been shown, in some cases, to reverse DIC and be successful. The use of recombinant activated factor VIIa should be considered in patients with massive obstetric hemorrhage in whom standard measures of stabilization are unsuccessful.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 7 publications
0
17
0
1
Order By: Relevance
“…Adjunctive therapy with tranexamic acid may be added to control excessive thrombolysis which may exacerbate the bleeding of DIC [19,20]. In extreme cases, when conventional therapy fails, anecdotal success has been reported with recombinant factor VIIa in patients with DIC and life-threatening bleeding [21,22]. However, the safety of this agent in the setting of DIC has not been studies [23].…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive therapy with tranexamic acid may be added to control excessive thrombolysis which may exacerbate the bleeding of DIC [19,20]. In extreme cases, when conventional therapy fails, anecdotal success has been reported with recombinant factor VIIa in patients with DIC and life-threatening bleeding [21,22]. However, the safety of this agent in the setting of DIC has not been studies [23].…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of some studies and individual reports, recombinant factor VIIa has been proposed for treatment of the coagulopathy associated with AFE (ref. 10,[37][38][39] ), although its efficacy is by no means established. Recombinant factor VIIa was used proportionately more frequently in Slovakia than in the UK; nevertheless the incidence of fatal AFE is higher in Slovakia.…”
Section: Discussionmentioning
confidence: 99%
“…The cytological analysis was based on central or peripheral venous blood smear by using fresh hematoxylin-erosin (H-E) dropped stain examined by two pathologists. The examination revealed fetal squamous with background of maternal erythrocytes [5]. The diagnosis of pulmonary edema or adult respiratory distress syndrome (ARDS) was based on the clinical features including moist rales heard from both lung bases and blood gas analysis or chest X-ray.…”
Section: Methodsmentioning
confidence: 99%
“…If patient has no response to cardiopulmonary resuscitation, postmortem cesarean section can be performed during the resuscitation [18]. Total hysterectomy and/or iliac embolization or recombinant factor VIIa was made by a multidisciplinary team as other authors have reported [2,5,19] Recombinant factor VIIa has been used successfully to treat postpartum hemorrhage in patients who do not have high circulating tissue factor concentrations, such as those with uterine atony, uterine rupture, and abnormal placentation [19]. However, it is recommended that recombinant factor VIIa should be considered only in AFE patients when the hemorrhage cannot be stopped by massive blood component replacement.…”
Section: Arch Gynecol Obstetmentioning
confidence: 99%